Comparison of fine‐needle aspiration and core‐needle biopsy in the pathological evaluation on thyroid lesions: A single‐center experience on 407 Chinese patients. Issue 5 (13th February 2023) - Li, Wei; Han, Ya‐Ting; Hu, Zhandong; Zhang, Yujie; Zhao, Xin; Guo, Xuexi; Cai, Wenjuan; Zhang, Mingfang
Abstract: Background: The object of this study was to compare the diagnosis performance of US‐guided fine‐needle aspiration (FNA) and core‐needle biopsy (CNB) for patients with thyroid nodules, in aspects of sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV). Materials and Methods: Four hundred seven Chinese patients from July 2019 to June 2022 were retrospectively recruited in this study. Cytological diagnoses were categorized into six categories based on the 2017 Bethesda System for Reporting Thyroid Cytopathology (BSRTC), and histological specimens were drawn a diagnosis by means of an analogy with the Bethesda system. Results: All patients incorporated were proceed with surgical excision (SE) and received final surgical diagnoses. The rate of malignancy (ROM) was comparable between two methods, with the exception that the test‐negative category of the FNA group was significantly higher than that of the CNB group (39.25% vs. 23.86%, p = .022). Sensitivity and accuracy were higher in CNB group (82.50% and 87.83%, respectively) than that in FNA group (72.00% and 79.36%, respectively), as well as NPV (76.14% in CNB vs. 60.75% in FNA), but not in terms of the specificity and PPV (95.59% and 97.30% in FNA vs. 97.10% and 98.02% in CNB). Conclusion: CNB displayed a higher sensitivity and accuracy than FNA in malignant lesions of thyroid. Both FNA and CNB exhibit excellent performance with the understanding that both need to be applied under the most appropriate conditions to maximize their benefits.